2017
DOI: 10.1155/2017/9514369
|View full text |Cite
|
Sign up to set email alerts
|

A Resting-State Brain Functional Network Study in MDD Based on Minimum Spanning Tree Analysis and the Hierarchical Clustering

Abstract: A large number of studies demonstrated that major depressive disorder (MDD) is characterized by the alterations in brain functional connections which is also identifiable during the brain's "resting-state." But, in the present study, the approach of constructing functional connectivity is often biased by the choice of the threshold. Besides, more attention was paid to the number and length of links in brain networks, and the clustering partitioning of nodes was unclear. Therefore, minimum spanning tree (MST) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 76 publications
(104 reference statements)
3
45
0
1
Order By: Relevance
“…High coherence between two EEG signals reflects synchronized neuronal oscillations (suggesting functional integration between neural populations), while low coherence indicates independently active populations (suggesting functional segregation) (Murias et al, 2007). Using EEG coherence to study the brain activity of patients with depression (Li et al, 2017), as well as those with Alzheimer's disease (AD) (Wada et al, 1998) and Parkinson's disease (Teramoto et al, 2016), has been quite successful. For example, Murias et al (2007) observed an elevated EEG theta coherence in the frontal and temporal regions of the left hemisphere in individuals with autism spectrum disorder.…”
Section: Introductionmentioning
confidence: 99%
“…High coherence between two EEG signals reflects synchronized neuronal oscillations (suggesting functional integration between neural populations), while low coherence indicates independently active populations (suggesting functional segregation) (Murias et al, 2007). Using EEG coherence to study the brain activity of patients with depression (Li et al, 2017), as well as those with Alzheimer's disease (AD) (Wada et al, 1998) and Parkinson's disease (Teramoto et al, 2016), has been quite successful. For example, Murias et al (2007) observed an elevated EEG theta coherence in the frontal and temporal regions of the left hemisphere in individuals with autism spectrum disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the goal of the current study was to examine global functional network connectivity and organization and detect the hubs between IA and controls in resting‐state EEG data. Studying the dynamics of spontaneous (independent‐task) activities in the brain provides us with meaningful information on how the different brain regions communicate and the functional brain network infrastructure (Fraga et al, ; Li et al, gies, such as fMRI (Khanna, Pascual‐Leone, Michel, & Farzan, ). In addition, although traditional graph theory analysis is helpful for understanding brain mechanisms, it still has the limitation of a lack of standard methods (van Diessen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the goal of the current study was to examine global functional network connectivity and organization and detect the hubs between IA and controls in resting-state EEG data. Studying the dynamics of spontaneous (independent-task) activities in the brain provides us with meaningful information on how the different brain regions communicate and the functional brain network infrastructure (Fraga et al, 2016;Li et al, 2017). EEG is inexpensive and has a millisecond time resolution, which is finer than the other neuroimaging technologies, such as fMRI (Khanna, Pascual-Leone, Michel, & Farzan, 2015).…”
mentioning
confidence: 99%
“…Fast independent component analysis was used for denoising to obtain more pure EEG signals, ensuring the effectiveness of the extracted features in the subsequent work. The ERD/ERS phenomenon is related to the mu (8-12 Hz) and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) rhythms of EEG signals. However, some frequencies in the beta rhythm are the harmonic waves of the mu rhythm.…”
Section: Eeg Data Preprocessingmentioning
confidence: 99%
“…MST is the only subnetwork in the weighted network that avoids methodological biases and solves the problem of network connectivity. Moreover, MST can simplify network characteristics and directly compare networks with the same number of nodes [18]. MST is a new and emerging method of human functional connectomics and has been effectively used in the recent research on some neuropsychiatric diseases [19].…”
Section: Introductionmentioning
confidence: 99%